ANALISIS YURIDIS PENGARUH USIA TERHADAP TINGGINYA TINGKAT PERCERAIAN DI KOTA BATAM (STUDI PENELITIAN DI PENGADILAN AGAMA KELAS IA BATAM) - Wardah Wasliati; Laily Washiati; Balqis Wasliati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This journal is entitled Juridical Analysis of the Effect of Age on the High Level of Divorce in Batam City (Research Study at the Religious Court Class Ia Batam) on Jalan RE. Martadinata Number 5, Sekupang, Batam City, Riau Islands 29425, with the construction problems: What are the legal arrangements regarding filing for divorce at the Batam Class IA Religious Court?; and what are the factors behind the high divorce rate in Batam and what are the solutions to reduce the high divorce rate? The qualification/type of writing for this journal uses a normative legal writing type, which is supported by sociological/empirical legal research. To analyze some of the problems in this journal, a big theory (The Pure Theory of Law) is used. Legal positivism (positive law school) which sees the need to clearly separate law and morals (between applicable law and the law that should be), and theory (Law is Command of a Lawgiver) John Austin, namely the law is considered as a logical system, fixed and closed (closed logical system), the law is strictly separated from justice and is not based on good and bad values. Legal arrangements regarding filing for divorce in the Religious Courts refer to Law Number 1 of 1974 concerning Marriage, Government Regulation of the Republic of Indonesia Number 9 of 1975 concerning the Implementation of Law Number of 1974 concerning Marriage, Law Number 32 of 1954 concerning Enforcement of Laws - Law of the Republic of Indonesia dated November 21, 1946 Number 22 of 1946 concerning Registration of Marriage, Divorce, Reconciliation in All Regions Outside Java and Madura, Instruction of the President of the Republic of Indonesia Number 1 of 1991 concerning the Dissemination of Compilation of Islamic Law, Law of the Republic of Indonesia Number 3 of 2006 concerning Amendments to Law Number 7 of 1989 concerning Religious Courts.Keywords: Marriage, Divorce, Age Effect.